Energy Ethics: The (Im)Purity of Renewable Energy Sources. An Analysis of Offshore Wind Farms in the Baltic Sea - Rup, Maja (Stan Rzeczy, 2025)
This article examines the ethical and environmental issues of offshore wind farms being developed on the Polish coast of the Baltic Sea. The main research questions are whether ethical energy production is possible, whether renewable energy sources, such as offshore wind farms, serve as truly ethical energy sources, and what environmental problems are associated with their operation. The study applies Alexis Shotwell’s concept of “impurity” and theoretical frameworks from the energy humanities, critical posthumanism, and feminist new materialism. The analysis reveals ethical paradoxes in renewable energy – while it does not directly emit greenhouse gases, its production and operation involve environmental burdens such as ecosystem disruption, resource extraction, and the reinforcement of neocolonial dependencies. The article highlights that achieving a more ethical energy production requires not only changing the source but also a reconsideration of energy consumption levels.